2000
DOI: 10.4095/211157
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the Wathaman Batholith and its relationship to the Archean Peter Lake Domain along the Reindeer Lake transect, Saskatchewan

Abstract: The Wathaman Batholith in Saskatchewan is a stitching pluton emplaced at the boundary between accreted volcano-sedimentary rocks of the La Ronge Domain and the Archean Hearne Province margin. Along the northern shore of Reindeer Lake, megacrystic granitoid rocks of the Wathaman suite intrude and host xenoliths of Archean gneiss of the Peter Lake Domain. The Swan River complex, which intrudes Archean gneiss of Peter Lake Domain, contains mafic-ultramafic sills including layered olivine gabbro and diorite. It lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Seismic profile S2b (see fig. 7 in Corrigan et al 2005) shows strong shallow northwestdipping reflectors in the juvenile La Ronge Domain, consistent with structures observed at surface (Corrigan et al 1999), as well as the south-vergent thrust stacking kinematics. The more seismically transparent upper crust of the Rottenstone is consistent with the steep fabrics and partial melting developed during the postaccretion collision (Corrigan et al 2005).…”
Section: Trans-hudson Orogeny In Central Canadasupporting
confidence: 80%
“…Seismic profile S2b (see fig. 7 in Corrigan et al 2005) shows strong shallow northwestdipping reflectors in the juvenile La Ronge Domain, consistent with structures observed at surface (Corrigan et al 1999), as well as the south-vergent thrust stacking kinematics. The more seismically transparent upper crust of the Rottenstone is consistent with the steep fabrics and partial melting developed during the postaccretion collision (Corrigan et al 2005).…”
Section: Trans-hudson Orogeny In Central Canadasupporting
confidence: 80%
“…the Park Island and Partridge Breast assemblages Corrigan et al 1998Corrigan et al , 1999Corrigan et al , 2001b. Both these units contain abundant detrital zircons originating from the juvenile La Ronge -Lynn Lake -Rusty Lake supracrustal belt, with a peak at c. 1.92-1.88 Ga (Tran et al 2008;D.…”
Section: Pericratonic Arc Accretion On Southeastern Hearne Craton Marmentioning
confidence: 99%
“…It was emplaced during a relatively narrow time interval between c. 1862 and 1850 Ma, in a continental arc setting (Fumerton et al 1984). The main body of the batholith is composed of K -feldspar megacrystic, biotite + hornblende + titanite-bearing granite, granodiorite and quartz monzonite, with lesser amounts of diorite and layered gabbro (Corrigan et al 1999). Along its northern flank, the batholith intrudes basement and cover sequences of the Hearne Craton margin.…”
Section: Wathaman -Chipewyan Batholithmentioning
confidence: 99%
“…2.63 Ga (Bickford et al 1987, Rayner et al 2005b tonalitic to granodioritic gneisses, primarily located in the northeast part of the domain along Reindeer Lake . A minor component within these gneisses are screens of mafic volcanic 1 rocks that contain Mg-rich ultramafic sills, as well as separate units of iron formation, migmatitic pelite, and felsic volcanic rocks (Lewry et al 1980, Ray and Wanless 1980, Corrigan et al 2000, Maxeiner et al 2010. Some of these supracrustal sequences might be correlative with the 2.72 to 2.68 Ga Rankin-Ennadai greenstone belt, exposed as outliers near the Saskatchewan/ NWT border, while others are 2.566 Ga (Maxeiner et al 2010).…”
Section: Regional Geologymentioning
confidence: 99%
“…Over time, the PLD's geological framework has been significantly revised and new ideas about the timing, distribution, and mode of formation of its contained PGE-occurrences have been formulated . Work by Corrigan et al (2000) and has revealed that the majority of the mafic rocks of the domain belong to two intrusive complexes, the 2.56 Ga Swan River complex and the 1.92 Ga Porter Bay complex. While the age, geochemistry and plate tectonic setting of the Porter Bay complex has been previously described , a similar approach is required for the Swan River complex.…”
Section: Introductionmentioning
confidence: 99%